Beyond Life Years Lost, Using Different Outcomes for Population Modelling in Tobacco Harm Reduction - Prasad Krishna; Hill Andrew; Fiebelkorn Stacy; Edward Lauren (Contributions to Tobacco and Nicotine Research)
Evaluating the reduced-risk potential of novel tobacco and nicotine products, as compared to cigarettes, requires consideration not only of individual risk but also the impact on the population as a whole. Where the reduction in health risk for smokers who switch to the product instead of continuing to smoke, but also the product’s potential effects and rate of uptake among non-smokers must be taken into account.